Missions in a changing world: The Bundeswehr and its operations abroad - Rainer Glatz; Wibke Hansen; Markus Kaim; Judith Vorrath (Stiftung Wissenschaft und Politik (SWP), 2018)
Military operations abroad by the German Armed Forces are always a controversial instrument of German crisis management. Yet, such foreign deployments are likely to remain necessary for the foreseeable future while, at the same time, they are undergoing noticeable change. The conditions shaping this transformation can be captured in three dimensions of change: the change in war and violent conflict; the transformation of the international political and legal context; and the shifting institutional frameworks for these operations. German policy-makers must address the related challenges - whether setting normative anchors and formats for operations, contributing to stabilisation in a context of continuing insecurity, building partners' military capacities, dealing with transnational threats or using benchmarks for exiting. Yet, they only have limited influence over the described changes. Fundamentally, decisions about military operations abroad are taken within the triangle of pressing problems (crises and conflicts), responsibility (obligations under international law, alliances, political commitments), and the political situation and available capabilities in Germany itself. It is hard to predict the developments which will dictate the scope for action within this triangle. However, the worst possible approach would be to address the described challenges only from a short-term and ad-hoc perspective, especially since they do not exclusively concern operations abroad. In its 2017 Guidelines on crisis prevention and conflict resolution and 2016 White Paper, the German federal government outlined a framework for German engagement that it now has to fill. Furthermore, the expectations of Germany's partners within the EU, NATO and UN have grown - which will also require further military contributions.
Keywords: 320